High-ranking alleviates male local competition in lek mating systems - Fabio Giavazzi (Nature Portfolio, 2018)
Abstract Territoriality entails demanding social interactions with competing individuals, typically males. Variation in quality of males can be predicted to affect the spatial arrangement of territories. We present a model aimed at understanding the spatial properties of territories on leks, where the presence of a hierarchy in a population of males leads to the clustering of individuals around high-ranking ‘hotshot’ males. The hierarchy results in a decrease in the number of nearest neighbors interacting directly with high-ranking males, with potential socio-sexual benefits for such males.